Specifying Challenges in Transcribing Covert Recordings: Implications for Forensic Transcription - Love, Robbie; Wright, David (Frontiers in Communication, 2021)
Covert audio recordings feature in the criminal justice system in a variety of guises, either on their own or accompanied by video. If legally obtained, such recordings can provide important forensic evidence. However, the quality of these potentially valuable evidential recordings is often very poor and their content indistinct, to the extent that a jury requires an accompanying transcript. At present, in many international jurisdictions, these transcriptions are produced by investigating police officers involved in the case, but transcription is a highly complex, meticulous and onerous task, and police officers are untrained and have a vested interest in the influence of the transcript on a case, which gives rise to potential inaccuracy. This paper reports the design and results of a controlled transcription experiment in which eight linguistically trained professional transcribers produced transcripts for an audio recording of a conversation between five adults in a busy restaurant. In the context of covert recordings, this recording shares many of the typical features of covert forensic recordings, including the presence of multiple speakers, background noise and use of non-specialist recording equipment. We present a detailed qualitative and quantitative comparison of the transcripts, identifying areas of agreement and disagreement in (a) speaker attribution and (b) the representation of the linguistic content. We find that disagreement between the transcriptions is frequent and various in nature; the most common causes are identified as (i) omission of speech that is included in other transcripts, (ii) variation in the representation of turns, (iii) orthographic variation seemingly motivated by phonetic similarity, and (iv) orthographic variation seemingly not motivated by phonetic similarity. We argue that the variable nature of the transcription of ‘challenging’ audio recordings must be considered in forensic contexts and make recommendations for improving practice in the production of forensic transcriptions.